SAS for Finance : Forecasting and data analysis techniques with real-world examples to build powerful financial models. - Gulati, Harish (Packt Publishing, 2018)
SAS is the ground-breaking tool for advanced, predictive, and statistical analytics. Right from refining your data using power of SAS analytics, you will be able to exploit the capabilities of high-powered package to create accurate financial models. You can easily assess the pros and cons of models to suit unique business needs.